Medicinal Properties of the Dog Grass - Cynodon Dactylon (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article provides a review of the literature on the healing properties of Cynodon dactylon (L.) Pers. Bermuda grass is a weed. Used in folk medicine of Central Asia, Bulgaria and Azerbaijan. It is rarely used in scientific medicine. It has anti-inflammatory, antioxidant, hypoglycemic, antiviral, immunomodulatory properties.